2006
DOI: 10.1080/09540260601039959
|View full text |Cite
|
Sign up to set email alerts
|

Mental health model of care programmes after the tsunami in Aceh, Indonesia

Abstract: Before the tsunami, there was no systematic training provided for General Practitioners (GPs) and nurses in issues related to mental health and psychosocial support in times of disasters. After the tsunami, the Department of Psychiatry, Faculty of Medicine, University of Indonesia in Jakarta was contracted to organize a special two-week intensive training programme on basic psychiatry for 13 GPs from Banda Aceh Mental Hospital. To improve the nursing practice, a Professional Nursing Practice Model (MPKP) has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 2 publications
0
23
0
1
Order By: Relevance
“…Higher values reflect higher PTSR, and thus poorer psychosocial health. Psychosocial counseling has been shown to mitigate the effects of disasters on psychosocial well-being, and efforts were made to strengthen mental health services in Aceh in the years following the disaster (Prasetiyawan et al 2006). We assess who obtained counseling.…”
Section: Data and Measurementmentioning
confidence: 99%
“…Higher values reflect higher PTSR, and thus poorer psychosocial health. Psychosocial counseling has been shown to mitigate the effects of disasters on psychosocial well-being, and efforts were made to strengthen mental health services in Aceh in the years following the disaster (Prasetiyawan et al 2006). We assess who obtained counseling.…”
Section: Data and Measurementmentioning
confidence: 99%
“…It is shown that QOL among patients with mental disorders was rated good or very good by 90-92% of those who saw friends or family at least weekly, those who attended social or leisure events or facilities at least monthly and those who felt they had at least three people that they could count on. In contrast, 72-79% of those with poorer social support rated their quality of life as high [13]. Thus, cadres are expected to affect favorably to the perception, attitude, and support of community toward the patients with mental disorders, which, in turn, contribute to the QOL among the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although their QOL can be increased by the support from the community, it is possible that the negative experiences in meeting those who have mental health problems are confounded by stigma and poor access to mental health services [13]. It is shown that QOL among patients with mental disorders was rated good or very good by 90-92% of those who saw friends or family at least weekly, those who attended social or leisure events or facilities at least monthly and those who felt they had at least three people that they could count on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, countries including Indonesia and Sri Lanka have established sustainable community mental health systems in disaster areas. 4,5 While Japan has an established mental health system, there is great room for improvement in community mental health especially in rural areas. In the existing situation, it would have been impossible for psychiatric clinics and hospitals to provide care to such large numbers of people.…”
mentioning
confidence: 99%